NILAI-NILAI RELIGIUS DALAM TEMBANG PAMOJHI RITUAL HODO MASYARAKAT ADAT SUKU PARIOPO - Ainun Najib; Mukhammad Baharun (LP2M Universitas Ibrahimy, 2020)
Hodo is a ceremonial ritual of Pariopo tribe in order to ask for rain. This ritual is survival ancestor since hundred of past which has endured to this day. In spite of development, this ritual changes and developments in line with the changing era and times. Behaviour and diversity society of Pariopo Tribe also influence changes in Hodo’s Ritual, because the society of Pariopo Tribe are 100% Moslems. Acculturation of cultural and religious values seems very united in the implementation of this ritual later. The unification between cultures and religious values can be seen from the poems of Pamojhi songs that were rebounded as long as Ritual takes place. Pamojhi’s songs depicted religious values of Islam which is very deep breath. It is the core of the religious teaching from the building joins of faith. The meaning of Pamojhi’s songs is one note withIslamic theology. The First is devotion, a belief where there is no God to worship except Allah. And the Second is petition and Connection, its mean of certainty about power of the one supreme which regulates al human life. So, the third is surrender, human of submission form slave to ruler after pass up petition or attempt to get something which be desired. These values are embodied in the magic spell ritual worship in the implementation of Hodo, either explicitly or implicitly, that the ritual could be accepted by society and survive until now.